Adult onset scapuloperoneal myopathy. Issue 10 (October 1975) - Thomas, P K; Schott, G D; Morgan-Hughes, J A
Abstract : Six cases are described of muscle weakness and wasting of scapuloperoneal distribution with an onset in early adult or middle life and a relatively benign progression. One case also showed mild facial weakness. Four cases were probably sporadic but in two, a mother and daughter, autosomal dominant inheritance was likely. Electromyographic studies demonstrated myopathic features in all, and this was confirmed by muscle biopsy in five. Electrocardiographic abnormalities were present in three cases, but their significance is uncertain. It is considered that adult onset scapuloperoneal myopathy constitutes a clinically distinct condition.